Contribución a la historia económica de Cartagho-Nova durante los siglos V y VI d. C.: el vertedero urbano de la calle Palas - Roldán Bernal, Blanca; López Campuzano, Manuel; Vidal Nieto, Milagros (Antigüedad y Cristianismo, 1991)
This article presents a preview of the results obtained from the arqueological excavations which were carried out in the Calle Palas, Cartagena In 1990. In this site it was posible to identify an area used as the city dump dated between the fifth and sixth centuries d.C. We think that this finding provides a valuable contribution to the economic history of Carthago Nova during this period.